Evaluation of the effect of gravity on the rotational loss of superconducting magnetic bearings for space applications. Issue 1 (1st August 2022) - Okumura, Satsuki; Onoue, Takemi; Ahmad, Doa; Terao, Yutaka; Ohsaki, Hiroyuki; Sakurai, Yuki; Matsumura, Tomotake; Katayama, Nobuhiko
Abstract: We study the relationship between the levitation gap change and losses in a superconducting magnetic bearing (SMB) system. We develop a polarization modulator bearing for a cosmic microwave background (CMB) polarization experiment. The heat generated by the polarization modulator needs to be kept very low. Therefore, it is essential to model the effect of the levitation gap change of a rotor due to gravity on the rotational loss. We have constructed a prototype small experimental platform of an axial-flux SMB with an array of high-temperature superconductors, YBCO, and a permanent magnet ring. In this system, the weight of the rotor can be set. We measured the effect of the change in the levitation gap of the rotor due to gravity on the loss. When the levitation force was 5.5 N and 16.0 N, the losses generated in the rotor were 9.1 × 10 −3 W and 1.6 × 10 −2 W, respectively. It was confirmed that the loss increases with the increase in the levitation force of the SMB.